Rigid-foldable tubular arches. (15th August 2017) - Gattas, Joseph M.; Lv, Weilin; Chen, Yan
Highlights: An experimental and numerical investigation is conducted on a new type of folded tubular arch. A common geometric description is developed between three types of tubular arches. A numerical study shows the double-kite arch developed in this paper has the highest failure load. This is the first investigation into the structural performance of rigid-foldable tubular arches. Abstract: Several types of tubular, origami-inspired plate mechanisms have been proposed for use as meta-materials and deployable structures. However, research into mechanical properties of these mechanisms is limited to rectilinear forms. This paper investigates the structural feasibility of non-rectilinear rigid-foldable cellular materials for application as deployable arch structures. An experimental and numerical investigation is first conducted on a new type of folded tubular arch, with failure contributions identified from hinge rotation and plate buckling failure mechanisms. A common geometric description is then developed between three different types of origami-inspired tubular arches, which are numerically investigated under three-point loading. The double-kite arch developed in this paper is seen to have the highest failure load.